Relationship between pediatric celiac disease and chromatin remodeling gene expressions - Boyacioglu, Seda; Caliskan, Metin; Dogan, Guzide (Genetika (Beograd), 2022)
Celiac disease (CD) is an immune-dependent systemic disorder that occurs in genetically predisposed individuals resulting in damage in the small intestine. It is known that chromatin remodeling, an epigenetic mechanism, is associated with gastrointestinal diseases associated with chronic inflammation. However, no information is available on the link between CD and chromatin remodeling. For this purpose, the expression profiles of chromatin remodeling group genes in children diagnosed with CD according to Marsh classification and HLA profile were evaluated and their relationship with CD was investigated. Endoscopic biopsies embedded in the paraffin block of 40 children with CD diagnosis and 30 healthy children were included in the study. The most common four mutations (DQA1*05, DQB1*02, DQA1*03, and DQB1*03:02) related to CD on human leukocyte antigen (HLA) gene were screened. Intestinal biopsy samples were used for mRNA isolations and cDNA synthesis. Expressions of total seven genes in the chromatin remodeling groups (SWI/SNF Complex Group: ARID1A, Polycomb Group: CTBP1, Nucleosome-Remodeling & Histone Deacetylase (NuRD) Complex Group: MTA1, Chromobox/Heterochromatin Protein 1 (HP1) Homologs Group: CBX3 and CBX7, Homeodomain (PHD) Protein Group: NSD1, Inhibitor of Growth (ING) family group: ING 5) were analyzed by Real-Time qPCR. Data analysis was performed online using the software provided by the manufacturer. Overexpression in ARID1A, CTBP1, and NSD1 genes was detected when the CD group was compared against the control group, however they were not significant (p=0.31, 0.33, and 0.33). When CD group who had diarrhea symptom (typical) were compared to the CD group without diarrhea symptom (atypical), statistically significant under-expression was found in CBX3 and CTBP1 genes (p=0.04 and p=0.004). Statistically significant CTB1 overexpression was detected in Marsh 2 CD cases (p=0.03). In the comparison of HLA DQ2/DQ8 positive CD patient group with the control group, the NSD1, CBX3, and EED (p=0.75, 0.75, and 0.78) genes were over-expressed and the CBX7, MTA1, ARID1A, and CTBP1 genes (p=0.74, 0.75, 0.75, and 0.75) were under-expressed. This is the first study to report that expression of chromatin remodeling genes may have roles in the development and progression of CD. The results of this case-control study are open to confirmation by future studies with larger number of subjects to obtain statistically significant results.